Influential Effect of Digital Smile Design on Orthodontic Treatment Decision - Mahmood, Rawasee; Jassim, Israa S.; Yassir, Yassir A. (Scientific Journal of Medical Research, 2022)
Objective: Since the psychological aspect is necessary for patients’ motivation for orthodontic treatment, this study aims to investigate the role of expectations or patient satisfaction on orthodontic treatment via using the Digital Smile Design (DSD) during the treatment planning. Methods: It is a cross-sectional experimental design involving 52 participants who are unsatisfied with their smiles and not certain about having orthodontic treatment; the participants have been identified and consented to participate in this study after receiving detailed information verbally. A mobile phone camera with a height-adjustable tripod and HP EliteBook 840 G1 portable computer has been used for photograph capturing in this study. After taking the participant’s photos and its export to the computer, a PowerPoint template for DSD was used to analyze the photo. Later on, present the pre and post-photo for the participant to evaluate the influence of the expected outcomes on his satisfaction for orthodontic treatment by giving a percentage. Results: In both Genders, Class I showed the highest percentage among other classes, in addition, crowding represents about three quarter of the cases compared to spacing, concerning their satisfaction it is found that Participants with Class I and II incisors are more satisfied than Class III Participant, while the crowding were more satisfied with DSD results compared to those with spacing. Conclusion: The DSD is a useful tool in the planning stage of orthodontic treatment and can be used as a visual aid to enhance patient’s expectations.